2014
DOI: 10.1152/jn.00729.2013
|View full text |Cite
|
Sign up to set email alerts
|

Encoding of graded changes in spatial specificity of prior cues in human visual cortex

Abstract: Prior information about the relevance of spatial locations can vary in specificity; a single location, a subset of locations, or all locations may be of potential importance. Using a contrast-discrimination task with four possible targets, we asked whether performance benefits are graded with the spatial specificity of a prior cue and whether we could quantitatively account for behavioral performance with cortical activity changes measured by blood oxygenation level-dependent (BOLD) imaging. Thus we changed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 130 publications
2
48
0
Order By: Relevance
“…The behavioral data presented here were divided into 2 training phases in order to match the data from the main EEG analysis, in which we tried to obtain ~400 trials for each experimental condition (10 EEG sessions for each training phase) as suggested by Luck [54]. In line with previous studies, Δc increased as a function of contrast (F(5, 55) = 143.38, p < 0.001) [9,28,52,5558] and decreased with focused compared to divided attention (F(1, 11) = 137.95, p < 0.001) [5,9,28,56]. These attentional modulations occurred at all contrast levels (all t(11)’s ≥ 5.03, all p ’s < 0.001, data collapsed across early and late training phases, false discovery rate [FDR]-corrected, 2-tailed).…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…The behavioral data presented here were divided into 2 training phases in order to match the data from the main EEG analysis, in which we tried to obtain ~400 trials for each experimental condition (10 EEG sessions for each training phase) as suggested by Luck [54]. In line with previous studies, Δc increased as a function of contrast (F(5, 55) = 143.38, p < 0.001) [9,28,52,5558] and decreased with focused compared to divided attention (F(1, 11) = 137.95, p < 0.001) [5,9,28,56]. These attentional modulations occurred at all contrast levels (all t(11)’s ≥ 5.03, all p ’s < 0.001, data collapsed across early and late training phases, false discovery rate [FDR]-corrected, 2-tailed).…”
Section: Resultssupporting
confidence: 80%
“…We used this task to make contact with previous studies in both humans and nonhuman primates that have employed similar paradigms [5,9,3638]. At the start of a trial, subjects were cued to attend to either the left or right lower visual quadrant (termed focused attention trials), or they were cued to attend to both locations (termed divided attention trials).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations